Mesenchymal stem cells for systemic therapy: Shotgun approach or magic bullets?. (26th November 2012) - Millard, Susan M.; Fisk, Nicholas M.
Abstract Given their heterogeneity and lack of defining markers, it is surprising that multipotent mesenchymal stem/stromal cells (MSCs) have attracted so much translational attention, especially as increasing evidence points to their predominant effect being not by donor differentiation but via paracrine mediators and exosomes. Achieving long‐term MSC donor chimerism for treatment of chronic disease remains a challenge, requiring enhanced MSC homing/engraftment properties and manipulation of niches to direct MSC behaviour. Meanwhile advances in nanoparticle technology are furthering the development of MSCs as vehicles for targeted drug delivery. For treatment of acute injuries, systemic cell‐free exosome delivery may ultimately displace current emphasis on empiric donor‐cell transplantation for anti‐inflammatory, immunomodulatory and repair‐promoting effects. Exploration of potential clinical sources of MSCs has led to increased utilisation of perinatal MSCs in allogeneic clinical trials, reflecting their ease of collection and developmentally advantageous properties.